Beyond Timber: forest management models for transforming conflict into cooperation - Ceci, Pierpaolo; Taedoumg, H.E.; Gotor, Elisabetta; Spedding, V. (Bioversity International, 2016)
The competing needs of different groups who depend upon the Congo Basin rainforest can be met if innovative, new research-based models for multiple-use forest management are employed.The models, together with accompanying policy guidance, have been endorsed by the region’s forest administration body COMIFAC and offer the potential to alleviate both the conflict between groups and the pressures on the landscape, allowing livelihoods and forest to flourish. Underpinned by groundbreaking, multi-disciplinary, international research, the models embody combined insights into local people’s needs, the ecological